Some Results of τ_1 τ_2 – d Semi connectedness and compactness in bi-topological Spaces - Arunmaran, M.; Kannan, K. (Hindawi, 2018)
We are going to establish some results of T1T2-d semiconnectedness and compactness in a bitopological space. Besides, we will investigate several results in T1T2-d semiconnectedness for subsets in bitopological spaces. In particular, we will discuss the relationship related to semiconnectedness between the topological spaces and bitopological space. Tat is, if a bitopological space (X, T1, T2) is T1T2-d semiconnected, then the topological spaces (X, T1) and (X, T2) are d-semiconnected. In addition, we introduce the result which states that a bitopological space (X, T1, T2) is T1, T2-d semiconnected if and only if X and are the only subsets of X which are T1, T2-d semiclopen sets. Moreover, we have proved some results in compactness also. Altogether, several results of T1, T2-d semiconnectedness and compactness in a bitopological space have been discussed